2015
DOI: 10.1021/ic5030636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Hybrid m-Terphenyl/o-Carborane Building Block: Applications in Phosphine Ligand Design

Abstract: A hybrid terphenyl/o-carborane ligand building block is synthesized by the reaction of m-terphenylalkyne with B10H14. This sterically demanding substituent can be installed into ligands, as demonstrated by the preparation of carboranylphosphine. The bulky phosphine reacts with [ClRh(CO)2]2 to produce monophosphine complex ClRhL(CO)2, which subsequently extrudes CO under vacuum to afford the dimeric species [ClRhL(CO)]2. The latter complex does not react with excess phosphine and is resistant toward cyclometala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the main application for exo ‐metallated carborane derivatives is in the field of catalysis , . Although the o ‐carborane moiety usually gets used because of its stability and bulky character,, the different inductive effects of the o ‐carborane moiety have also been used to modulate the coordinating ability of vicinal sulfur and phosphorus donor atoms in coordination compounds. Thus, a thioether group shows reduced donor ability when connected to a C‐ m ‐carboranyl moiety, but presents enhanced donor strength when connected to the antipodal boron atoms of o ‐ and m ‐carborane groups .…”
Section: Introductionmentioning
confidence: 99%
“…However, the main application for exo ‐metallated carborane derivatives is in the field of catalysis , . Although the o ‐carborane moiety usually gets used because of its stability and bulky character,, the different inductive effects of the o ‐carborane moiety have also been used to modulate the coordinating ability of vicinal sulfur and phosphorus donor atoms in coordination compounds. Thus, a thioether group shows reduced donor ability when connected to a C‐ m ‐carboranyl moiety, but presents enhanced donor strength when connected to the antipodal boron atoms of o ‐ and m ‐carborane groups .…”
Section: Introductionmentioning
confidence: 99%
“…Carboranes are usually deemed as polyhedral boranes with one or more BH vertices being replaced by CH ones, recognized as three-dimensional inorganic benzene analogues. Indeed, they are termed as “superaromatic” and exhibit extraordinary thermal stability as well as unusual chemical reactivity such as electrophilic substitution, similar to that of planar aromatics. Owing to their unique steric/electronic properties, many applications in drug design, as well as in materials and organometallic/coordination chemistry have been found. And a growing interest has been directed toward the design and synthesis of complexes that combine carborane clusters and aromatic units. Moreover, it has been reported that carboranes linked organic groups fulfill many requirements of optical luminescence and nonlinearity. Thus, continuing our interest in the study of carborane complexes, , a new member of the family of high-performance NLO materials were discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Their unique characteristics such as thermal and chemical stabilities as well as three-dimensional structures make them attractive building blocks for boron neuron capture therapy agents in medicine, [2] functional units in supramolecular design/materials, [3] and versatile ligands in organometallic/coordination chemistry. [4] Recent results have also demonstrated that cage carbon-arylated o-carboranes are ac lass of AIE (aggregation induced emission) active and stimuli-responsive luminescent materials,thus exhibiting very interesting photophysical properties,w here the carborane moiety plays aunique role. [5] These arylated o-carboranes are generally prepared from the condensation reaction of decaborane with the corresponding aryl or diaryl acetylenes, [6] and the yields of the desired products are variable.…”
mentioning
confidence: 99%
“…Thes ame yield was obtained with 40 equivalents of benzene in dichloromethane (DCM), while Abstract: Photoarylation of iodocarboranes with unactivated arenes/heteroarenes at room temperature has been achieved, for the first time,t hus leading to the facile synthesis of al arge variety of cage carbon mono(hetero)arylated and di-(hetero)arylated o-carboranes.T his work represents ac lean, efficient, transition-metal-free,a nd cheap synthesis of functionalized carboranes,w hich has significant advantages over the knownmethods. the yield of 3awas decreased if 20 equivalents of benzene was used (entries [3][4][5][6]. Other solvents and bases did not improve the yield of 3a (entries [8][9][10][11][12][13][14].…”
mentioning
confidence: 99%